2002
DOI: 10.1128/aem.68.2.634-641.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Substrate Specificity of Nitrobenzene Dioxygenase from Comamonas sp. Strain JS765

Abstract: Comamonas sp. strain JS765 can grow with nitrobenzene as the sole source of carbon, nitrogen, and energy. We report here the sequence of the genes encoding nitrobenzene dioxygenase (NBDO), which catalyzes the first step in the degradation of nitrobenzene by strain JS765. The components of NBDO were designated Reductase NBZ , Ferredoxin NBZ , Oxygenase NBZ␣ , and Oxygenase NBZ␤ , with the gene designations nbzAa, nbzAb, nbzAc, and nbzAd, respectively. Sequence analysis showed that the components of NBDO have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 32 publications
(33 reference statements)
6
129
0
Order By: Relevance
“…13D) is then used to complete metabolism of 3-methylcatechol to TCA cycle intermediates (62). Subsequent growth assays showed that JS42 is also able to grow on nitrobenzene (111). Cloning and sequencing of the genes encoding 2-nitrotoluene dioxygenase (2NTDO) revealed that it is a Rieske-type nonheme iron dioxygenase (later verified by biochemical analysis of the purified protein [146]) which has high sequence similarity to naphthalene dioxygenase from Pseudomonas sp.…”
Section: Pathways For Nitrotoluene Catabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…13D) is then used to complete metabolism of 3-methylcatechol to TCA cycle intermediates (62). Subsequent growth assays showed that JS42 is also able to grow on nitrobenzene (111). Cloning and sequencing of the genes encoding 2-nitrotoluene dioxygenase (2NTDO) revealed that it is a Rieske-type nonheme iron dioxygenase (later verified by biochemical analysis of the purified protein [146]) which has high sequence similarity to naphthalene dioxygenase from Pseudomonas sp.…”
Section: Pathways For Nitrotoluene Catabolismmentioning
confidence: 99%
“…13C). Biochemical and genetic analyses of nitrobenzene dioxygenase (NBDO) showed that it belongs to the naphthalene family of multicomponent Rieske-type dioxygenases (111). Crystal structures and site-directed mutagenesis studies of NBDO identified the active site of the enzyme, as well as key amino acids that bind and direct oxidation specifically to the nitrosubstituted carbon (48,91).…”
Section: Pathways For Nitrobenzene Catabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…PNP was monitored at 280 nm with an Agilent ultraviolet detector, and its retention time was 11.2 min. The NH 4 + (Fawcett and Scott 1960) and NO 2 − (Lessner et al 2002) concentrations were colorimetrically detected (Chi et al 2013). The concentration of nitrate (NO 3 − ) was determined as described by Norman et al (1985).…”
Section: Soil Microcosm Experimentsmentioning
confidence: 99%
“…Substrate specificity of naphthalene, 2-nitrotoluene and nitrobenzene dioxygenases. The genes for the nitrobenzene dioxygenase (NBDO) system and the 2-nitrotoluene dioxygenase (2NTDO) system have been cloned and sequenced (6,8) and the gene organization is shown in Fig. 5.…”
Section: D)mentioning
confidence: 99%